Evaluation of the effectiveness of cadet training programs in competency development and learning in Timor-Leste - Mauzino, Albino; Costa, Henrigue da (Creative Smart Visionary, 2025)
This study aims to evaluate the effectiveness of the new cadet training program of the Timor Leste National Police in the development of competencies and learning. Using a quantitative approach with a quasi-experimental design (one-group pre-test and post-test), this study involved 60 cadets as a sample. Data was collected through validated objective test instruments, then analyzed using descriptive statistics, the Paired Sample t-Test, and the Gain Score. The results showed a significant increase between pre-test and post-test scores (p < 0.001), with an average gain score of 0.43 in the medium category. Evaluation based on the CIPP (Context, Input, Process, Product) model revealed that although the training succeeded in improving the technical competence of cadets, there is still room for improvement in aspects of the training process, especially in the integration of experience-based learning. The study concluded that the effectiveness of training was partial and emphasized technical readiness rather than mental and contextual readiness. The implications of these results encourage the need to reformulate training approaches to be more adaptive to the learning challenges and tasks of contemporary policing.